Antioxidační enzymy - biochemické markery oxidačního stresu - Matoušková, Martina; Ruttkay-Nedecký, Branislav; Kizek, René (Journal of Metallomics and Nanotechnologies, 2014)
Oxidative stress is the imbalance between the oxygen radicals and antioxidant defence system of the organism and leads to cell damage. Antioxidant enzymes are an important part of the defense against oxidative stress and the crucial ones are superoxide dismutase, catalase, glutathione peroxidase and glutathione reductase. Superoxide dismutase catalyses the conversion of superoxide to hydrogen peroxide, which can be further degraded by catalase to oxygen and water. Peroxidases are enzymes catalysing the reduction of the number of peroxides to alcohols. Glutathion peroxidases are selenium dependent enzymes using reduced glutathione (GSH) as a cofactor. They catalyze the conversion of hydrogen peroxide to water while the reduced glutathione is oxidized. The GSH is then being renewed by the activity of glutathione reductase, another antioxidative enzyme that reduces oxidized glutathione (GSSG) to GSH.
Keywords: Oxidative Stress; katalasa; Superoxide Dismutase; Antioxidants; antioxidancia; Glutathione Reductase; oxidační stres; glutathionreduktasa; glutathionperoxidasa; Catalase; superoxiddismutasa; Glutathione Peroxidase